Genome-wide association analysis in primary sclerosing cholangitis - Karlsen, Tom H.; Franke, Andre; Melum, Espen; Kaser, Arthur; Hov, Johannes Roksund; Balschun, Tobias; Lie, Benedicte A.; Bergquist, Annika; Schramm, Christoph; Weismüller, Tobias J.; Gotthardt, Daniel; Rust, Christian; et al. (Gastroenterology, 2010)
We aimed to characterize the genetic susceptibility to primary sclerosing cholangitis (PSC) by means of a genome-wide association analysis of single nucleotide polymorphism (SNP) markers.
Online veröffentlicht am 26. November 2009
Gesehen am 02.03.2023